Climate Change Projections in the Upper Gilgel Abay River Catchment, Blue Nile Basin Ethiopia - Adem, Anwar A.; Melesse, Assefa M.; Tilahun, Seifu A.; Setegn, Shimelis Gebriye; Ayana, Essayas K.; Wale, Abeyou; Assefa, Tewodros T. (2014)
openalex: W39739855 mag: 39739855
Keywords: openalex:import

Climate Change Impact on Sediment Yield in the Upper Gilgel Abay Catchment, Blue Nile Basin, Ethiopia - Adem, Anwar A.; Tilahun, Seifu A.; Ayana, Essayas K.; Worqlul, Abeyou W.; Assefa, Tewodros T.; Dessu, Shimelis Behailu; Melesse, Assefa M. (2015)
According to Intergovernmental Panel on Climate Change (IPCC) future projections, precipitation and temperature will increase over eastern Africa in the coming century. This chapter presents basin-level impact of climate change on sediment yield in Upper Gilgel Abay catchment, Blue Nile Basin, Ethiopia, by downscaling HadCM3 global climate model using Statistical Downscaling Model (SDSM). IPCC-recommended baseline period (1961–1990) was used for baseline scenario analysis. Future scenario analysis was performed for the 2020s, 2050s, and 2080s. Globally, HadCM3 model is widely applied for climate change studies and it consists of A2 (medium high emission) and B2 (medium low emission) scenarios. Impact assessment on sediment yield was done by Soil and Water Assessment Tool (SWAT) hydrological model. SWAT model performance in simulating daily sediment yield for the study area was satisfactory with Nash–Sutcliffe Efficiency (NSE) of 0.58 and 0.51 for calibration and validation periods, respectively. Mean annual changes of precipitation and temperature (maximum and minimum) were applied to quantify these impacts. The result of downscaled precipitation and temperature reveals a systematic increase in all future time periods for both A2 and B2 scenarios. These increases in climate variables are expected to result in increase in mean annual sediment yield of 11.3, 16.3, and 21.3 % for A2 scenario and by 11.0, 14.3, and 11.3 % for B2 scenario for the 2020s, 2050s, and 2080s, respectively. This increase in sediment yield is double the increase in stream flow due to climate change for all time periods. Future work need to consider also impact of land use change on the catchment for future sustainable development plan.
openalex: W1035230204 mag: 1035230204
Keywords: openalex:import

Climate Change Impact on Stream Flow in the Upper Gilgel Abay Catchment, Blue Nile basin, Ethiopia - Adem, Anwar A.; Tilahun, Seifu A.; Ayana, Essayas K.; Worqlul, Abeyou W.; Assefa, Tewodros T.; Dessu, Shimelis Behailu; Melesse, Assefa M. (2015)
According to Intergovernmental Panel on Climate Change (IPCCIPCC ) future projectionsAdem, A.A. , precipitationAyana, E.K. and temperatureTilahun, S.A. will increase over easternWale, A. Africa in the coming century. This chapter presents basin-level impact of climate changeClimate change on stream flow in Upper Gilgel Abay catchmentUpper Gilgel Abay Catchment , Blue Nile basin,Blue Nile Basin EthiopiaEthiopia , by downscaling HadCM3HadCM3 global climate model (GCM) using statistical downscalingStatistical downscaling model (SDSM). IPCC recommended baseline period (1961–1990) was used for analysis of baseline scenario. For future scenario analysis time periods of the 2020s, 2050s and 2080s were used. Globally, HadCM3 model is widely applied for climate change studies and it contains A2 (medium–high emission) and B2 (medium–low emission) scenarios. The impact assessment on stream flow was done using the soil and water assessment tool (SWATSWAT ) hydrological model. The performance of SWAT model in simulating the stream flow was shown with a Nash–Sutcliffe Efficiency (NSE) of 0.76 and 0.78 for calibration and validation periods, respectively. Mean annual changes of precipitation and temperature (maximum and minimum) were applied to quantify these impacts. The result of downscaled precipitation and temperature reveals a systematic increase in all future time periods for both A2 and B2 scenarios. These increases in climate variables are expected to increase mean annual stream flow by 7.1, 9.7, and 10.1 % for A2 scenario and by 6.8, 7.9, and 6.4 % for B2 scenario for 2020s, 2050s, and 2080s, respectively. Future work need to consider impact of land use change on the catchment for future sustainable development plan.
openalex: W1001812396 mag: 1001812396
Keywords: openalex:import